Skeletal Tissue Mechanics - Martin, R. Bruce; Burr, David B.; Sharkey, Neil A.; Fyhrie, David P. (Springer New York : Imprint: Springer, 2015)
This textbook describes the biomechanics of bone, cartilage, tendons and ligaments. It is rigorous in its approach to the mechanical properties of the skeleton yet it does not neglect the biological properties of skeletal tissue or require mathematics beyond calculus. Time is taken to introduce basic mechanical and biological concepts, and the approaches used for some of the engineering analyses are purposefully limited. The book is an effective bridge between engineering, veterinary, biological and medical disciplines and will be welcomed by students and researchers in biomechanics, orthopedics, physical anthropology, zoology, and veterinary science. This book also: Maximizes reader insights into the mechanical properties of bone, fatigue and fracture resistance of bone, and mechanical adaptability of the skeleton Illustrates synovial joint mechanics and mechanical properties of ligaments and tendons in an easy-to-understand way Provides exercises at the end of each chapter.